Pengaruh Laba Rugi Perusahaan, Pergantian Manajemen, Dan Financial Distress Terhadap Audit Report Lag - Susanti, Dewi Sri; Challen, Auliffi Ermian; Elmanizar, Elmanizar; Ikhsan, Arfan (Asosiasi Dosen Akuntansi Indonesia, 2023)
This study aims to determine the effect of the company profit and loss, management changes, and financial distress on audit report lag. The population in this study are consumer goods industry companies listed on the Indonesia Stock Exchange (IDX). The sample was used in as many as 20 companies obtained through the purposive sampling method. The data used in this research is secondary data. The method used to analyze the data in this study is multiple linear regression. Based on the results of the study, it was concluded that the company profit and loss had a negative effect on audit report lag, management changes had a positive effect on audit report lag, and financial distress did not affect audit report lag